2017
DOI: 10.18203/2394-6040.ijcmph20170468
|View full text |Cite
|
Sign up to set email alerts
|

A study on demographic and clinical profile of children with extra hepatic portal venous obstruction and with special reference to thrombophilic factors

Abstract: Background: Extra-hepatic portal vein obstruction (EHPVO) due to portal vein thrombosis is an important cause of portal hypertension in several region including India. The cause of thrombosis in these patients remains unclear. Objective of the study was to study the demographic features, etiology, clinical, laboratory findings with special reference to thrombophilic factors like protein C, protein S and antithrombin III deficiency in children with EHPVO.Methods: The prospective analysis of 62 patients of EHPVO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Table X showed that no significant association was observed between EHPVO and non EHPVO for antithrombin III deficiency. However, the odds for EHPVO due to low antithrombin III level were 12.25 (95% CI: 17,18 The wide variation in the frequencies of antithrombin III deficiency implies the impact of geographic and ethnic variations among patients as the mentioned studies were done in different parts of the world like Denmark and India respectively.…”
Section: Table-vi: Endoscopic Findings Of Antithrombin III Deficient ...mentioning
confidence: 99%
“…Table X showed that no significant association was observed between EHPVO and non EHPVO for antithrombin III deficiency. However, the odds for EHPVO due to low antithrombin III level were 12.25 (95% CI: 17,18 The wide variation in the frequencies of antithrombin III deficiency implies the impact of geographic and ethnic variations among patients as the mentioned studies were done in different parts of the world like Denmark and India respectively.…”
Section: Table-vi: Endoscopic Findings Of Antithrombin III Deficient ...mentioning
confidence: 99%
“…Liver function is mostly well preserved, unless compromised by reduced hepatic cell mass and synthetic dysfunction, as rarely seen with advanced age, prolonged duration of disease, and development of SBC from PB [7]. Neonatal exchange transfusion through umbilical catheterisation, omphalitis, congenital abnormalities, childhood sepsis, and prothrombotic disorders, like deficiencies in the naturally occur-ring anticoagulants (protein c, protein s, and antithrombin III) and factor V leiden and prothrombin gene mutations, are some of the suspected reasons [2].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Extra hepatic portal venous obstruction (EHPVO) is the most common cause of non-cirrhotic portal hypertension (NCPH) in Indian children, particularly affecting lower socio-economic strata [1]. Neonatal and childhood septic conditions, and prothrombotic disorders are some of the suspected reasons [2]. Upper gastrointestinal (GI) bleeding is most common presentation of EHPVO.…”
Section: Introductionmentioning
confidence: 99%